Developmental dynamics of intergroup contact and intergroup attitudes: Long-term effects in adolescence and early adulthood - Wölfer, R; Schmid, K; Hewstone, M; van Zalk, M (Wiley, 2016)
The combined use of high resolution X-ray computed tomography with digital image correlation allows quantitative observations of the three-dimensional deformations that occur within a material when it is strained. In suitable microstructures, the displacement resolution is sub-voxel (a voxel is the three-dimensional equivalent of a pixel), and both elastic and plastic deformations can be studied. This paper reviews recent work in which three-dimensional in situ observations of deformation have provided unique insights that support both continuum and heterogeneous microstructure-dependent models of damage development in a range of materials. The examples presented include; crack propagation in a quasi-brittle porous material (polygranular graphite), sub-indentation radial and lateral cracking in a brittle polycrystalline ceramic (alumina); plastic deformation and damage development underneath indentations in a ductile metal (Al-SiC composite) and a ceramic matrix composite (SiC-SiCfibre). These examples show how material properties can be obtained by analysis of the displacement fields, how such measurements can be used to better define the applied loading on small test specimens and how crack opening magnitude and mode may be extracted also. Some new directions for research are outlined, including the combined use of diffraction and imaging techniques on synchrotron X-ray facilities to map both elastic and inelastic strains.